Immunological cross-reactivity between anti-vitellogenin antibodies and vitellogenin in three species of catfish - Othman, Roshani; Harmin, Sharr Azni; Mohtar, Siti Hasmah; Sulong, Moohamad Ropaning; Mohd Zan, Mohd Syahril; Mohd Sulperi, Zarirah (Asia Life Sciences, 2021)
Vitellogenin (Vtg) is a specific biomarker of egg yolk precursor protein that is abundant in circulatory blood and indicates reproductive status in female fish and endocrine disruption in male fish. The protein highly conserved in various forms of Vtg in specific species. The aims of this study was to evaluate the cross-reactivity between Hemibagrus nemurus Vtg polyclonal antibody and vitellogenin from other catfish, Hemibagrus wyckiodes, Pangasius pangasius and Clarias gariepinus by enzyme-linked immunosorbent assay (ELISA). The plasma of three species of catfish was characterized using 7.5% SDS-PAGE and revealed a major polypeptide band corresponding to 100-175 kDa in H. wyckiodes, 70-160 kDa in Pangasius pangasius and 95-160 kDa in Clarias gariepinus and the existence of Vtg has been confirmed. The optimal detection of the H. nemurus Vtg was at dilution of 1/1000 polyclonal antibody. Furthermore, cross-reactivity tests showed that polyclonal antibody specific to H. nemurus Vtg reveals a cross-reaction with the plasma Vtg from three species of catfish. Thus, the polyclonal antibody can be used to detect and quantify Vtg in the three species of catfish that are closely related in order to examine the vitellogenesis periods and oocyte maturation.